Income Inequality and Poverty in Colombia - Part 1. The Role of the Labour Market - Joumard, Isabelle (OECD Economics Department Working Papers, 2013)
Income inequality in Colombia has declined since the early 2000s but remains very high by international standards. Income dispersion largely originates from the labour market, which is characterised by a still high unemployment rate, a pervasive informal sector and a wide wage dispersion reflecting a large education premium for those with higher education. Reducing income inequality is a key government objective and this requires improving the performance of the labour market. Raising educational outcomes for all and enhancing training programmes would help improve labour supply and productivity. Formal job creation however remains heavily constrained by restrictive labour market regulations, in particular very substantial non-wage labour costs and a minimum wage which is high compared to average incomes. The 2012 tax reform reduces non-wage labour costs but more decisive steps are needed to create the right conditions and incentives to boost formal employment